Beyond body and mind: Leisure of trade union workers in activities of the workers’ recreation service on Ilha das Flores in the 1940s and 1950s - Santos, Victor da Costa (Revista do Instituto Histórico e Geográfico Brasileiro, 2024)
Home to an immigrant guesthouse between 1883 and 1966, the island Ilha das Flores served other purposes during this period. Besides being used as a prison during both Great Wars, the area on the island reserved for receiving immigrants was also used for promoting the leisure of trade union workers between the 1940s and 1950s. The activities held by the Workers’ Recreation Service took place on the island at a time when the guesthouse was under the administration of the Ministry of Labor. Seen from this angle, such activities would represent one of the facets of Vargas’ labor ideology that has yet to be studied, namely treating leisure as a public asset.